2016
DOI: 10.1021/acs.jpcb.5b11643
|View full text |Cite
|
Sign up to set email alerts
|

General Applicable Frequency Map for the Amide-I Mode in β-Peptides

Abstract: In this work, a general applicable amide-I vibrational frequency map (GA map) for β-peptides in a number of common solvents was constructed, based on a peptide derivative, N-ethylpropionamide (NEPA). The map utilizes force fields at the ab initio computational level to accurately describe molecular structure and solute-solvent interactions, and also force fields at the molecular mechanics level to take into account long-range solute-solvent interactions. The results indicate that the GA map works reasonably fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…The application of VSMs of amide modes is not limited to polypeptides and proteins composed of -amino acids. Recently, Wang and coworkers theoretically determined the coefficients to calculate the amide I frequency of N-ethylpropionamide (NEPA), a model compound of -amino acid, based on electrostatic potentials on the N, H, C and O atoms of the peptide unit, 331 and the calculated linear spectra of NEPA in three different solvents were in reasonable agreement with the experimental results. They also computed the coupling strengths of the amide I and II modes for five helical -peptide conformers, 332,333 and showed that the coupling strengths for shorter inter-amide distances cannot be described well by the TDC model.…”
mentioning
confidence: 60%
“…The application of VSMs of amide modes is not limited to polypeptides and proteins composed of -amino acids. Recently, Wang and coworkers theoretically determined the coefficients to calculate the amide I frequency of N-ethylpropionamide (NEPA), a model compound of -amino acid, based on electrostatic potentials on the N, H, C and O atoms of the peptide unit, 331 and the calculated linear spectra of NEPA in three different solvents were in reasonable agreement with the experimental results. They also computed the coupling strengths of the amide I and II modes for five helical -peptide conformers, 332,333 and showed that the coupling strengths for shorter inter-amide distances cannot be described well by the TDC model.…”
mentioning
confidence: 60%
“…70,71 Similarly, to IR spectra of natural proteins and peptides, the amide I and II absorption bands, originating mainly from C]O stretching and N-H bending vibrations ($1651 and $1540 cm À1 ) of the peptide backbone were considered. [72][73][74] The amide I vibration depends on the backbone structure and is commonly used for secondary structure analysis by tting with components bands or by decomposing into basis spectra. 75 The most intense contribution of deconvoluted amide I band of 1 in HFIP is at 1648 cm À1 which could be assigned to a random coil conformation (Table S1 †).…”
Section: Structure and Morphologymentioning
confidence: 99%
“…This work drove the early development and subsequent widespread use of IR spectroscopy for structural analysis. (2) In turn, spectroscopic models that facilitate the interpretation of amide I spectra were extensively developed. Models for similar carbonyl stretches in ketones, acetyls, aldehydes, and esters remain comparatively undeveloped. , (3) With some exceptions, the protein backbone represents a uniform array of oscillators with one-to-one correspondence between oscillators and protein residues. Backbone CO stretches are vibrationally coupled and form delocalized modes that reflect the underlying arrangement of the oscillators, namely the protein structure. , …”
Section: Introductionmentioning
confidence: 99%